(3eHGOF GdEbJUGO (B:s (3GdJMdjd GdLRFj (B/s - (3YQjbGJ, MQHj eMeO ehSis ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2005)
(3eaGgje CSGSjI aj Yde GdEbJUGO(B- (3fXQjGJ GdbjeI(B- (3fXQjI GdWdH(B- (3fXQjI GdYQV(B- (3JhGRf GdWdH hGdYQV(B- (3fXQjI Sdhc GdeSJgdc(B- (3fXQjI GdEfJGL(B- (3fXQjI JcGdja GdEfJGL(B- (3fXQjI GdJhRjY(B- (3fXQjI GdGShGb(B- (3JhGRf GdefJL aj MGdGJ GdGShGb GdeNJdaIs
Keywords: (3GdEbJUGOs; (3GdJMdjd GdEbJUGOjs